Geology of the Mulkhura River Valley, Georgian Caucasus - Roman M. Kumladze; Levan G. Tielidze; Mamia Gamkrelidze; Simon J. Cook; Anzor Giorgadze (Geosciences)
Geological mapping provides vital information about the structure, evolution, natural resource potential, and geohazards of a specific area. The role of geological mapping is especially valuable for mountainous countries like Georgia. In this context, we present a geological map of the Mulkhura River Valley in the Georgian Caucasus (43°3′ N, 42°52′ E) with accompanying cross-sections at a scale of 1:30,000, covering approximately 220 km2. The geological information in the map is based on a comprehensive review of previously published geological maps and literature, combined with original analysis of satellite imagery and hitherto unpublished field data. The extensive spatial coverage and accompanying cross-sections provide detailed insights into the structure of the region. This new map will serve as a foundation for future geological research, hazard management, and resource exploration in the area, as well as for geoconservation to develop the national geotourism industry in this region.